(untitled) - Geoffrey Lean (Santa Barbara, California, 1994)
The book provides the most up-to-date report possible on the state of the world's environment. With over 200 full-color maps and diagrams, the book explains what is happening to our planet - including disappearing forests, acid rain, climate change, pollution, and desertification
Keywords: atlases,man - influence on nature